IMPLEMENTATION OF THE PICTURE AND PICTURE METHOD IN IMPROVEMENT EFFORTS THE ABILITY TO TELL PUPPET STORIES FOR CLASS VIII C STATE MTS PREMBUN - Dwiyanti, Afriliyah (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2022)
This study aims to describe the steps for learning storytelling skills in wayang stories using the picture and picture method for class VIII C students of MTs Negeri Prembun for the 2017/2018 school year; improving the ability to tell stories in wayang stories using the picture and picture method for class VIII C students at MTs Negeri Prembun for the 2017/2018 school year. The subjects of this study were students of class VIII C MTs Negeri Prembun, totaling 28 students. This research consists of three stages, namely pre-cycle activities, cycle I, and cycle II. Each cycle refers to the research procedure, namely planning, acting, observing, and reflecting. Data was collected by using test and non-test techniques. The data analysis technique was in the form of qualitative descriptive analysis. The steps for learning wayang storytelling consist of three activities, namely pre-cycle, cycle I, and cycle II. The implementation of the actions in cycle II uses the picture and picture method; (2) The results of the pre-cycle scores on average reached 66.61, from 28 students there were 22 students who had not completed, and 6 students who had completed. This value belongs to the less category. Then there was an increase in the average value in the first cycle reaching 75.18. This score is quite sufficient, because of the 28 students only 19 students whose scores are above the completion limit and 9 students have not completed. In the category of completeness the value in pre-cycle activities is 20%, in the first cycle it is 67%, while in the second cycle it is 100%. This shows that the picture and picture method can improve students’ abilities and learning outcomes in learning wayang storytelling.